Efficacy and safety of maintenance olaparib and bevacizumab in ovarian cancer patients aged ≥65 years from the PAOLA-1/ENGOT-ov25 trial - Sabatier, Renaud; Rousseau, Frédérique; Joly, Florence; Cropet, Claire; Montégut, Coline; Frindte, Johanna; Cinieri, Saverio; Guerra Alía, Eva M.; Polterauer, Stephan; Yoshida, Hiroyuki; Vergote, Ignace; Colombo, Nicoletta; et al. (European journal of cancer, 2023)
Background - The phase III PAOLA-1/ENGOT-ov25 study (NCT02477644) showed that addition of olaparib to bevacizumab maintenance improved progression-free survival (PFS) in patients with newly diagnosed advanced ovarian cancer. We evaluated maintenance olaparib plus bevacizumab in older patients in PAOLA-1. - Methods - Baseline clinical and molecular data, and PFS, were compared between older (aged ≥65 years) and younger patients (<65 years). Factors associated with olaparib efficacy, and safety in age subgroups, were also assessed. - Results - Of 806 randomised patients, 292 (36.2%) were ≥65 years. A lower proportion of older versus younger patients had an Eastern Cooperative Oncology Group performance status of 0 (61.0% versus 76.2%) and upfront surgery (42.0% versus 55.7%). Older patients were less likely to have a BRCA1/2 mutation (17.1% versus 36.7%) or homologous recombination deficiency-positive status (34.1% versus 55.7%). After median follow-up of 22.1 months, median PFS was 21.6 months with olaparib versus 16.6 months with placebo in the older population (hazard ratio [HR] 0.55, 95% confidence interval [CI] 0.41-0.75), comparable with the younger population (median 22.9 versus 16.9 months; HR 0.61, 95% CI 0.49-0.77). PFS benefits were observed in patients with a BRCA mutation or homologous recombination deficiency-positive tumours. Incidence of olaparib-related grade ≥3 adverse events in older patients was comparable with that of younger patients (36.8% versus 31.7%) although hypertension and anaemia were more common in older patients. No treatment-related deaths occurred in older patients receiving olaparib. - Conclusion - Older patients enrolled in PAOLA-1 achieved similar PFS benefits compared with younger patients, with a similar safety profile.
Online verfügbar: 10. Dezember 2022, Artikelversion: 10. Januar 2023
Gesehen am 08.08.2023